International criminal justice at the Yugoslav tribunal a judge's recollection - Shahabuddeen, M., 1931- (Oxford : Oxford University Press, 2013)
Bringing together Judge Shahabuddeen's thoughts on the tribunal on which he served for many years, this book provides an insider's account of the development of international criminal law at the International Criminal Tribunal for the former Yugoslavia.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: International Tribunal for the Prosecution of Persons Responsible for Serious Violations of International Humanitarian Law Committed in the Territory of the Former Yugoslavia since 1991.; Yugoslav War Crime Trials, Hague, Netherlands, 1994-; Criminal procedure (International law)